2013
DOI: 10.1086/674327
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Sildenafil and Dobutamine in the Hypertrophic and Failing Right Heart in Vivo

Abstract: The purpose of this study was to investigate whether acute intravenous administration of the phosphodiesterase type 5 (PDE-5) inhibitor sildenafil in a single clinically relevant dose improves the in vivo function of the hypertrophic and failing right ventricle (RV). Wistar rats (n ¼ 24) were subjected to pulmonary trunk banding (PTB) causing RV hypertrophy and failure. Four weeks after surgery, they were randomized to receive an intravenous bolus dose of sildenafil (1 mg/kg; n ¼ 7), vehicle (n ¼ 6), or dobuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Previous studies have shown that sildenafil has little effect on TAPSE, supporting the notion that sildenafil does not have intrinsic effects on the myocardium [2, 20]. Additionally, systolic function parameters do not indicate any vasodilatory effect of sildenafil, but suggest the lack of an inotropic effect of sildenafil [2, 20]. These findings are consistent with another previous study, which showed that sildenafil has slightly positive intrinsic inotropic effects [19].…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies have shown that sildenafil has little effect on TAPSE, supporting the notion that sildenafil does not have intrinsic effects on the myocardium [2, 20]. Additionally, systolic function parameters do not indicate any vasodilatory effect of sildenafil, but suggest the lack of an inotropic effect of sildenafil [2, 20]. These findings are consistent with another previous study, which showed that sildenafil has slightly positive intrinsic inotropic effects [19].…”
supporting
confidence: 88%
“…Sm is an index of right ventricular systolic function and is well correlated with the right ventricular ejection fraction as derived from magnetic resonance imaging [29]. Previous studies have shown that sildenafil has little effect on TAPSE, supporting the notion that sildenafil does not have intrinsic effects on the myocardium [2, 20]. Additionally, systolic function parameters do not indicate any vasodilatory effect of sildenafil, but suggest the lack of an inotropic effect of sildenafil [2, 20].…”
mentioning
confidence: 99%
“…A direct inotropic effect of NO-sGC-cGMP stimulation has previously been hypothesized, but published results are few and conflicting. 14,[30][31][32][33][34] Sildenafil and riociguat decreased RV/LV ratio both in end systole and end diastole, indicating attenuation of RV dilatation and improved emptying of the RV, presumably due to afterload reduction. This was further indicated by an increase in RV stroke volume in animals treated with sildenafil.…”
Section: Effects Of No-sgc-cgmp Stimulationmentioning
confidence: 97%
“…Right heart failure is the terminal event of several diseases causing sustained pressure-overload of the right ventricle (RV), including pulmonary arterial hypertension (PAH), chronic thromboembolic pulmonary hypertension (CTEPH), and various congenital heart diseases. 1 3 Despite extensive research in the field, 4 8 there is still a lack of safe and effective targeted therapies for the right heart. Characterization of currently used pharmacologic agents with a potential beneficial effect on the right ventricle and development of new treatments for the right heart are required.…”
Section: Introductionmentioning
confidence: 99%